Model Sistem Penunjang Keputusan Untuk Pengelolaan Pembiayaan Nasabah Di BPR Sehat Sejahtera Universitas Pamulang - Afrizal Zein; Emi Sita Eriana (Institut Sains dan Teknologi Nasional, 2023)
Abstract One of the BPRs that is currently developing in South Tangerang is BPR Sehat Sejahtera. BPR Sehat Sejahtera is part of the Pamulang University Sasmita Group, whose function as a bank is to channel financing to community businesses so that they are able to support the country's economy. To distribute financing, BPR managers are expected to be able to conduct financing analysis to reduce the risk of financing failure. Until now, financing analysis carried out by BPRs tends to be manual and requires quite a long time to make financing decisions. One method that can be used to assist in financing analysis is the credit scoring model. To facilitate decision making, an SPK was formed with a credit scoring model to provide several choices regarding customer financing applications. The DSS development process follows the traditional software development stages, namely: (1) planning, (2) analysis, (3) design and (4) implementation. SPK is developed using a spreadsheet model with a dialog display that supports user needs. The credit scoring model developed uses several methods, namely discriminant analysis, multiple linear regression, logistic regression, and decision trees. Each method will produce a different credit scoring model to be included in the SPK model base. The SPK prototype developed resulted in several financing analyzes according to the credit scoring model used. The prediction accuracy shown by credit scoring models ranges from 70% -80%. This method is capable of producing a model that provides a fairly high predictive accuracy. Meanwhile, the decision tree method is still not optimal in producing a credit scoring model. Keywords: financing analysis, discriminant analysis, BPR, credit scoring, decision tree, multiple linear regression, logistic regression, decision support system (DSS)